Factors influencing the long term outcome of neurotization to the musculocutaneous nerve in traumatic bracial plexus injury - Mohammad Azrul Abdul Rashid
This study intended to evaluate the long term functional outcome of neurotization to the musculocutaneous nerve in traumatic brachial plexus injury (BPI) and the factors that might influence the functional outcome. Patients who were diagnosed with panplexus BPI and upper trunk BPI who underwent neurotization to musculocutaneous nerve in order to reanimate the elbow flexors were enrolled in this study. Patients with panplexus BPI underwent neurotization using spinal accessory nerve and patients with upper trunk BPI underwent neurotization using ulnar or median nerves as a donor. Post-operative outcomes were assess with Disabilities of the Arm, Shoulder and Hand (DASH) score and elbow flexor power using Medical Research Council grading. Factors that influencing the functional outcome of the procedure such as age, effect of injury to dominant hand, smoking status, timing of surgery, associated injuries and post-operative rehabilitation were evaluated. There were 70 patients recruited in this study with 31 patients had panplexus BPI and 39 patients had upper trunk BPI. The mean age of the patients was 23 years old. 11 patients with panplexus BPI had a good post-operative elbow flexor recovery (MRC grade 4-5) and 7 patients had a good post-operative DASH score (more than 50 points). 28 patients with upper trunk BPI had a good post-operative elbow flexors recovery and 29 patients had good post-operative DASH score. Time plateau of recovery for upper trunk BPI was 8 months and for panplexus was 13 months. Associated injuries to the patients and compliance to specific post-operative rehabilitation protocols were found to be statistically affecting the long term functional outcome of neurotization to the musculocutaneous nerve. In conclusion, upper trunk BPI has a better prognosis and outcome as compare to panplexus BPI